Microfoundations of Organizational Growth: Consequences for Entry Strategies and Financing of New Ventures - Obu, Osiebuni Collins; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2022)
An enormous number of firms fail to deliver economically profitable growth in output even though they may have strong managerial teams and adequate capital. In this paper, we provide new empirical evidence to demonstrate a few fundamental factors that can account for the ability of a firm to achieve economically sustainable scaling. In a bid to achieve that, we surveyed and discussed the prevailing theories that have established various grounds for organizational growth. On the basis of these theories, we hypothesized about the likely microfoundations for organizational growth. We went further to test these hypotheses using empirical data for all publicly-listed Nordic firms over a lengthy span of time, specifically ranging from 1990 to 2020. To implement the test, we established an econometric model, which is predicated on variables that we argued are capable of serving as a proxy for the microfoundations identified. It is our submission that effective and sustainable attainment of growth in output requires a new entrant to develop strategies that are centered on innovative products, as well as target highly concentrated industries, which are characterized by large markets, while financing such economic activities using equity capital as against debt capital.